2023
DOI: 10.3390/pharmaceutics15051328
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Recent Advances of Photodynamic Therapy for Primary Cutaneous Lymphomas

Abstract: Primary cutaneous lymphomas are rare non-Hodgkin lymphomas consisting of heterogeneous disease entities. Photodynamic therapy (PDT) utilizing photosensitizers irradiated with a specific wavelength of light in the presence of oxygen exerts promising anti-tumor effects on non-melanoma skin cancer, yet its application in primary cutaneous lymphomas remains less recognized. Despite many in vitro data showing PDT could effectively kill lymphoma cells, clinical evidence of PDT against primary cutaneous lymphomas is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The idea of our study was to assess the impact of the PDT on skin cells, fibroblasts, and keratinocytes, to assess its immunomodulatory effect and possible possibilities of its use in inflammatory skin diseases such as atopic dermatitis (AD) and psoriasis. In our experiment, hypericin was chosen as the photosensitizer (PS), whose properties have previously attracted the attention of many researchers [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of our study was to assess the impact of the PDT on skin cells, fibroblasts, and keratinocytes, to assess its immunomodulatory effect and possible possibilities of its use in inflammatory skin diseases such as atopic dermatitis (AD) and psoriasis. In our experiment, hypericin was chosen as the photosensitizer (PS), whose properties have previously attracted the attention of many researchers [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study population included 169 patients, and, after 6 weeks of treatment, HY–PDT was 49% more effective than placebo after 3 cycles. There were no serious drug-related side effects [ 30 , 31 ]. Additionally, Rook et al confirmed, in a phase II placebo-controlled study, the effectiveness of photodynamic therapy with topical hypericin and visible light irradiation in the treatment of cutaneous T-cell lymphoma and psoriasis [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…PSs can also transfer energy to triplet oxygen in the ground state ( 3 O 2 ) through a Type II reaction to generate highly reactive singlet oxygen, 1 O 2 . In the end, the reactive species produced during the photodynamic process destroy cancer cells directly through apoptosis, necrosis, or autophagy, as well as indirectly by injuring the tumour vascularity, which causes tumour ischemia [29]. It is important to note that both Type I and Type II reactions can occur at the same time.…”
Section: The Principles Of Photodynamic Therapymentioning
confidence: 99%
“…Photodynamic therapy (PDT) utilizing photosensitizing agents (such as 5-aminolevulinic acid [ALA]) irradiated with a specific wavelength of light in the presence of oxygen is being explored in CTCL ( 40 , 41 ). Limiting the use of ALA-PDT in CTCL is the poor tissue penetration of the photosensitizers, though new developments in the use of PDT for CTCL, such as innovative photosensitizers beyond ALA, more effective delivery methods deeper into lymphoma lesions, and novel prepping methods, are ongoing ( 42 ).…”
Section: Advances In Skin-directed Therapiesmentioning
confidence: 99%